Effect of diltiazem on exercise capacity after heart transplantation. Issue 8 (21st July 2017) - Varnado, Sara; Peled‐Potashnik, Yael; Huntsberry, Ashley; Lowes, Brian D.; Zolty, Ronald; Burdorf, Adam; Lyden, Elizabeth R.; Moulton, Michael J.; Um, John Y.; Raichlin, Eugenia
Abstract: Background: Sinus tachycardia (ST) is common after heart transplantation (HTx). The aim of the study was to evaluate the effect of diltiazem treatment during the first year after HTx on heart rate (HR), cardiac allograft function, and exercise capacity. Methods: From the total cohort, 25 HTx recipients started diltiazem treatment 4±2 weeks after HTx and continued it for at least 1 year (diltiazem group). Each study case was matched to a control. All patients underwent hemodynamic assessment and cardiopulmonary exercise test (CPET) at 1 year after HTx. Results: HR decreased in the diltiazem group from 99±11 bpm to 94±7 bpm ( P =.03) and did not change in the controls (98±11 bpm vs 100±13 bpm, P =.14). The difference between the groups at 1 year after HTx was significant ( P =.04). In the diltiazem group left ventricular (LV), stroke volume and ejection fraction increased (48±16 vs 55±17 mL, P =.02, and 60%±10% vs 62%±12% P =.03, respectively) but did not differ from controls. E/E' decreased (10.7±2.7 vs 7.3±1.9, P =.003) while cardiac index was higher (3.5±0.8 vs 3.1±0.5; P =.05) in the diltiazem group at 1‐year follow‐up. The absolute peak VO2 (21±4 vs 18±6 mL/kg/min; P =.05) and normalized peak VO2 (73%±17% vs 58%±14%; P =.004) were significantly higher in the diltiazem group. Conclusions: This study showed that diltiazem treatment reduces ST, may improve cardiac allograft function and exercise tolerance during the first year after HTx.